How to Create and Randomize a Vegenere Cipher Key Based on the Key Procedure of RC4+ Algorithm - Taronisokhi Zebua; Eferoni Ndruru (The IJICS (International Journal of Informatics and Computer Science), 2019)
The security of data not only depends on the complexity of the algorithm used, but one of the more important things to safeguard is key. The vegenere cipher algorithm is one of the common and easy to implement algorithms, but this algorithm is very easy to break with kasiki techniques by analyzing the word of cipher and keyword that have repetitive patterns. The RC4+ algorithm has the advantage of generating and generating fairly random keys. This research describes how to use the RC4+ key generation procedure to create and randomized the keys used in the vegenere cipher algorithm, to decrease recurrence of the same character of the cipher and character of the key